REGULARITIES OF SPATIO-TEMPORAL SPRING FLOOD RUNOFF OF THE MARMARIK RIVER (Proceedings of the YSU C: Geological and Geographical Sciences, 2011)
This work studies and analyses the regularities of spatial-temporal distribution of spring flood characteristics of the Marmarik River basin. For that purpose, the results of observations at water-measuring observation posts (the Marmarik River–Hanqavan Observation Post, the Marmarik River–Aghavnadzor Post, the Ulashik River–Artavaz Post, the Gomur River–Meghradzor Post) were collected, processed and evaluated for the period of 1936–2008. Close correlation links have been established between the average balanced height and flood runoff layer, the duration of high-water period. A map of spatial distribution of runoff layer of the flooding period (mm) has been drawn; runoff layer growth can be observed by height. According to the findings, in the Marmarik River basin there is tendency of flood runoff decrease, the start of flooding has shifted to winter period, its end-towards summer, depending on the growth of the air temperature in the basin. The complete study may serve as a basis for forecasting the flood runoff of the basin.
Keywords: Marmarik River basin; water-measuring observation posts; flooding period